Comparative lethal and sublethal toxicity of some conventional insecticides against tomato leafminer, Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) (Journal of the Entomological Research Society, 2022)
This study was conducted to introduce effective agent(s) among some novel and conventional insecticides in the management of Tuta absoluta (Meyrick, 1917), the most destructive insect pest of tomato throughout the world, in the lethal and sublethal terms of features. Toxicity of five chemical pesticides, including azadirachtin, emamectin benzoate, imidacloprid, lambda-cyhalothrin, and thiacloprid, was determined on 2nd-instar larvae of T. absoluta in the laboratory. The least LC50 value was attained with emamectin benzoate (0.52 mg A.I./L) among tested insecticides. Demographic parameters of the pest, including GRR (gross reproductive rate), R0 (net reproductive rate), rm (intrinsic rate of increase), T (mean generation time), and Î» (finite rate of increase) along with larval, pupal, and pre-adult periods were more affected by emamectin benzoate and azadirachtin. Adult pre-oviposition period (APOP), female and male longevities, oviposition period, and fecundity were low by emamectin benzoate. In the treatments by emamectin benzoate and azadirachtin the survival of fourth-instar larvae, pupae, and adults of insect was reduced in comparison to control. Accordingly, based on the highest adverse possessions of emamectin benzoate and azadirachtin on survival, life history, and demographic parameters of T. absoluta, the applicability of other tested insecticides imidacloprid, lambda-cyhalothrin, and thiacloprid may be limited.